Spatiotemporal variations and potential influencing factors of hemorrhagic fever with renal syndrome: A case study in Weihe Basin, China - Lingli Zhu; Liang Lu; Shujuan Li; Hongyan Ren (Public Library of Science (PLoS), 2023)
Background Hemorrhagic fever with renal syndrome (HFRS) is a widespread zoonotic disease seriously threatening Chinese residents' health. HFRS of Weihe Basin remains highly prevalent in recent years and attracts wide attention. With the acceleration of urbanization and related environmental changes, the interaction among anthropogenic activities, environmental factors, and host animals becomes more complicated in this area, which posed increasingly complex challenges for implementing effective prevention measures. Identifying the potential influencing factors of continuous HFRS epidemics in this typical area is critical to make targeted prevention and control strategies. Methods Spatiotemporal characteristics of HFRS epidemic were analyzed based on HFRS case point data in Weihe Basin from 2005 to 2020. MaxEnt models were constructed to explore the main influencing factors of HFRS epidemic based on HFRS data, natural environment factors and socioeconomic factors. Results Results showed that the HFRS epidemics in Weihe Basin were temporally divided into three periods (the relatively stable period, the rapid rising period, and the fluctuating rising period) and were spatially featured by relatively concentrated in the plains alongside the Weihe River. Landscape played controlling effect in this area while land use, vegetation and population in the area interacted with each other and drove the change of HFRS epidemic. The potential high-risk area for HFRS epidemic was 419 km2, where the HFRS case density reached 12.48 cases/km2, especially in the northern plains of Xi'an City. Conclusion We suggested that the temporal and spatial variations in the HFRS epidemics, as well as their dominant influencing factors should be adequately considered for making and/or adjusting the targeted prevention and control strategies on this disease in Weihe Basin. Author summary In recent years, the incidence rate of hemorrhagic fever with renal syndrome (HFRS) has declined in most area of China, although the acceleration of urbanization caused increasingly complicated interactions among anthropogenic activities, environmental factors, and host animals during the past decades. However, there were still some typical regions with serious HFRS epidemics in this country like the Weihe Basin in Shaanxi Province, in which more efforts should be paid for identifying the potential influencing factors and their driving mechanisms. Our study employed the MaxEnt modeling to reveal the spatio-temporal variations in the influencing factors on the epidemics of this disease from 2005 to 2020 in the Weihe Basin. We found that the landscape played controlling effect in this area while land use, vegetation and population in the area interacted with each other and drove the change of HFRS epidemic. The underling influencing factors and the stimulation of HFRS epidemic would provide detailed information for targeted strategy formulation, and the also provide reference for similar studies.